Effects of saline water and temperature on surface properties of HTV silicone rubber - Ali, M.; Hackam, R. (IEEE transactions on dielectrics and electrical insulation, 2008)
A study of the loss of hydrophobicity of high temperature vulcanized (HTV) silicone rubber (SIR) after immersion in saline solutions as a function of time (0 to 3000 h) at different temperatures is reported. The hydrophobicity is determined by measuring the static contact thetas between the tangent to the droplet of distilled water and the horizontal surface of the HTV SIR. The conductivity of the saline solution was varied from 0.005 to 100 mS/cm and the temperature from 0 to 98°C during immersion. The contact angle decreased from the original value of 100±4.6deg to low value of 15deg after 3000 h of immersion at 98°C in a solution of 0.005 mS/cm. The lower the conductivity, the larger was the decrease in the contact angle. The changes in the weight of the HTV SIR due to the uptake of water and the average surface roughness (ASR) are determined during the immersion. The increase/decrease in the weight and surface roughness of the HTV SIR are correlated with the contact angle and hence with the loss of hydrophobicity. The surface free energies Γ sd , Γ sh and Γ s , the interfacial energy of HTV SIR and water Γ sl , and the energy of adhesion W si of water on HTV SIR are determined as a function of time during the immersion and related to the loss of hydrophobicity.